The Glass Slipper : Women and Love Stories - Weisser, Susan Ostrov (Book collections on Project MUSE., 2013)
This book is about the persistence of a familiar Anglo-American love story into the digital age. The author compares diverse narratives, historical and contemporary from high literature and "low" genres, discussing novels by Jane Austen and Charlotte Brontë, Victorian women's magazines, and D.H. Lawrence's Lady Chatterley's Lover; romantic movies; popular Harlequin romance novels; masochistic love in films; pornography and its relationship to romance; and reality TV and Internet ads as romantic stories.